Alexandra Zheleznova-Armfelt: Rysk tonsättarinna med rötter i Sverige - Rukopolev, Vsevolod; Öhrström, Eva (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 1994)
Alexandra Zheleznova (1870–1933) was a composer in S:t Petersburg, member of the Swedish noble family Armfelt. The composer’s grandson draws a subjective picture of Alexandra Armfelt’s life and work as a musician and composer, characteristic of the role of music in the higher social classes of that time. As a child Alexandra recieved a musical education and started to compose. Her first work was published in 1894. Alexandra was recognised as a composer and was a member of the circle around Anton Rubinstein and Milij Balakirev. In 1895 Alexandra was married to the officer Vladimir Zheleznov. A stay in the Ural district 1896–1897 lead to an interest in folk music instruments and to the publishing of a booklet of cosack songs. During the years 1903–1914 she composed a number of romances and music for cello, violin and piano. With the revolution of 1917 the society and the culture that was the foundation for Alexandra’s work came to an end. Eventually she got to work as a pianist in a cinema and giving piano lessons. The article is concluded with a list of published and unpublished works.